# Thread: How many cocks does a cocksucker suck if a cocksucker sucks cock?

1. Tag huntin aint the way to go man.

2. Originally Posted by iTzSeyeko
i suck at math.
That's not the only thing you suck.

Jk, couldn't resist.

3. ## The Following User Says Thank You to Aborted For This Useful Post:

Pineapple Expressso (10-23-2013)

4. Originally Posted by Aborted

That's not the only thing you suck.

Jk, couldn't resist.
7/10. Needed more dicks.

5. Originally Posted by Aborted

That's not the only thing you suck.

Jk, couldn't resist.
i was waiting for it
but can't flame me no mores

6. Op is begging for Cs.

7. You really want CS.. don't you?

8. Well you *****

9. getting cs is like getting bullied all the time at school

10. Thou shall ask, and I shall deliver.

11. ## The Following 8 Users Say Thank You to arunforce For This Useful Post:

Confin3d (10-24-2013),Destenyofenemy (10-24-2013),Diamond (10-24-2013),Distraught (10-24-2013),Euphemistic (10-24-2013), (10-24-2013),[MPGH]Raple (10-24-2013),Assistive (10-24-2013)

12. Hahaha cocksucker.

x^2 - 562xy - 512x

Factor this lol smartasses .

13. Originally Posted by Kenshin13 Jr
Hahaha cocksucker.

x^2 - 562xy - 512x

Factor this lol smartasses .
Simplifying
x2 + -562xy + -512x = 0

Reorder the terms:
-512x + -562xy + x2 = 0

Solving
-512x + -562xy + x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-512 + -562y + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve:

Simplifying
x = 0

Solving
x = 0

Move all terms containing x to the left, all other terms to the right.

Simplifying
x = 0
Subproblem 2

Set the factor '(-512 + -562y + x)' equal to zero and attempt to solve:

Simplifying
-512 + -562y + x = 0

Reorder the terms:
-512 + x + -562y = 0

Solving
-512 + x + -562y = 0

Move all terms containing x to the left, all other terms to the right.

Add '512' to each side of the equation.
-512 + x + 512 + -562y = 0 + 512

Reorder the terms:
-512 + 512 + x + -562y = 0 + 512

Combine like terms: -512 + 512 = 0
0 + x + -562y = 0 + 512
x + -562y = 0 + 512

Combine like terms: 0 + 512 = 512
x + -562y = 512

Add '562y' to each side of the equation.
x + -562y + 562y = 512 + 562y

Combine like terms: -562y + 562y = 0
x + 0 = 512 + 562y
x = 512 + 562y

Simplifying
x = 512 + 562y

Solution

x = {0, 512 + 562y}

14. Originally Posted by unknownartist0

Simplifying
x2 + -562xy + -512x = 0

Reorder the terms:
-512x + -562xy + x2 = 0

Solving
-512x + -562xy + x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-512 + -562y + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve:

Simplifying
x = 0

Solving
x = 0

Move all terms containing x to the left, all other terms to the right.

Simplifying
x = 0
Subproblem 2

Set the factor '(-512 + -562y + x)' equal to zero and attempt to solve:

Simplifying
-512 + -562y + x = 0

Reorder the terms:
-512 + x + -562y = 0

Solving
-512 + x + -562y = 0

Move all terms containing x to the left, all other terms to the right.

Add '512' to each side of the equation.
-512 + x + 512 + -562y = 0 + 512

Reorder the terms:
-512 + 512 + x + -562y = 0 + 512

Combine like terms: -512 + 512 = 0
0 + x + -562y = 0 + 512
x + -562y = 0 + 512

Combine like terms: 0 + 512 = 512
x + -562y = 512

Add '562y' to each side of the equation.
x + -562y + 562y = 512 + 562y

Combine like terms: -562y + 562y = 0
x + 0 = 512 + 562y
x = 512 + 562y

Simplifying
x = 512 + 562y

Solution

x = {0, 512 + 562y}
Haha no, you did it wrong..

15. Originally Posted by unknownartist0

Simplifying
x2 + -562xy + -512x = 0

Reorder the terms:
-512x + -562xy + x2 = 0

Solving
-512x + -562xy + x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-512 + -562y + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve:

Simplifying
x = 0

Solving
x = 0

Move all terms containing x to the left, all other terms to the right.

Simplifying
x = 0
Subproblem 2

Set the factor '(-512 + -562y + x)' equal to zero and attempt to solve:

Simplifying
-512 + -562y + x = 0

Reorder the terms:
-512 + x + -562y = 0

Solving
-512 + x + -562y = 0

Move all terms containing x to the left, all other terms to the right.

Add '512' to each side of the equation.
-512 + x + 512 + -562y = 0 + 512

Reorder the terms:
-512 + 512 + x + -562y = 0 + 512

Combine like terms: -512 + 512 = 0
0 + x + -562y = 0 + 512
x + -562y = 0 + 512

Combine like terms: 0 + 512 = 512
x + -562y = 512

Add '562y' to each side of the equation.
x + -562y + 562y = 512 + 562y

Combine like terms: -562y + 562y = 0
x + 0 = 512 + 562y
x = 512 + 562y

Simplifying
x = 512 + 562y

Solution

x = {0, 512 + 562y}
mfw you can't even write the original problem

16. Originally Posted by Kenshin13 Jr
Haha no, you did it wrong..
Simplifying
x2 + -562xy + -512x = 0

Reorder the terms:
-512x + -562xy + x2 = 0

Solving
-512x + -562xy + x2 = 0

Move all terms containing y to the left, all other terms to the right.

Add '512x' to each side of the equation.
-512x + -562xy + 512x + x2 = 0 + 512x

Reorder the terms:
-512x + 512x + -562xy + x2 = 0 + 512x

Combine like terms: -512x + 512x = 0
0 + -562xy + x2 = 0 + 512x
-562xy + x2 = 0 + 512x
Remove the zero:
-562xy + x2 = 512x

Add '-1x2' to each side of the equation.
-562xy + x2 + -1x2 = 512x + -1x2

Combine like terms: x2 + -1x2 = 0
-562xy + 0 = 512x + -1x2
-562xy = 512x + -1x2

Divide each side by '-562x'.
y = -0.9110320285 + 0.001779359431x

Simplifying
y = -0.9110320285 + 0.001779359431x

Originally Posted by Trevor Phillips

mfw you can't even write the original problem
I believe in what I posted the problem is Equal to 0. So it solves it from there?

17. Originally Posted by unknownartist0

Simplifying
x2 + -562xy + -512x = 0

Reorder the terms:
-512x + -562xy + x2 = 0

Solving
-512x + -562xy + x2 = 0

Move all terms containing y to the left, all other terms to the right.

Add '512x' to each side of the equation.
-512x + -562xy + 512x + x2 = 0 + 512x

Reorder the terms:
-512x + 512x + -562xy + x2 = 0 + 512x

Combine like terms: -512x + 512x = 0
0 + -562xy + x2 = 0 + 512x
-562xy + x2 = 0 + 512x
Remove the zero:
-562xy + x2 = 512x

Add '-1x2' to each side of the equation.
-562xy + x2 + -1x2 = 512x + -1x2

Combine like terms: x2 + -1x2 = 0
-562xy + 0 = 512x + -1x2
-562xy = 512x + -1x2

Divide each side by '-562x'.
y = -0.9110320285 + 0.001779359431x

Simplifying
y = -0.9110320285 + 0.001779359431x

I believe in what I posted the problem is Equal to 0. So it solves it from there?
Your online calculator is broken bro.

Page 2 of 4 First 1234 Last